2010
DOI: 10.1007/s10822-010-9326-8
|View full text |Cite
|
Sign up to set email alerts
|

Design, structure-based focusing and in silico screening of combinatorial library of peptidomimetic inhibitors of Dengue virus NS2B-NS3 protease

Abstract: Serine protease activity of the NS3 protein of Dengue virus is an important target of antiviral agents that interfere with the viral polyprotein precursor processing catalyzed by the NS3 protease (NS3pro), which is important for the viral replication and maturation. Recent studies showed that substrate-based peptidomimetics carrying an electrophilic warhead inhibit the NS2B-NS3pro cofactor-protease complex with inhibition constants in the low micromolar concentration range when basic amino acid residues occupy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 52 publications
0
26
0
2
Order By: Relevance
“…The use of computational biology, bioinformatics and high-throughput screening was helpful in searching new antiviral drug for dengue [21].The high throughput screen helps identify and understand the molecular structure of virus for prediction of binding to the newly developed drug candidates. For example, screening of a combinatorial library of peptidomimetic inhibitors of dengue virus NS2B-NS3 protease [22]. It is only logical to screen these drugs for ZIKV.…”
Section: Development Of Antivirals and Therapeuticsmentioning
confidence: 99%
“…The use of computational biology, bioinformatics and high-throughput screening was helpful in searching new antiviral drug for dengue [21].The high throughput screen helps identify and understand the molecular structure of virus for prediction of binding to the newly developed drug candidates. For example, screening of a combinatorial library of peptidomimetic inhibitors of dengue virus NS2B-NS3 protease [22]. It is only logical to screen these drugs for ZIKV.…”
Section: Development Of Antivirals and Therapeuticsmentioning
confidence: 99%
“…The positions of the inhibitor P1, P2, P3 and P4 are related to the pockets S1, S2, S3 and S4 in this receptor, respectively. 6,[11][12][13] Pharmacologic therapy is absent for Dengue fever. Several research groups have begun medicinal chemistry projects using rational approaches.…”
Section: -4mentioning
confidence: 99%
“…The structures of the investigated peptides ( Figure 1) were obtained from a previous report 11 and generated using the GaussView 5.0 software program. 49 Compounds with basic functional groups were kept in their protonated forms.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same period, QSAR modeling of DENV2 NS2B/NS3pro inhibitor was also developed on peptidomimetic compounds using LUDI scoring function [28]. The MLR method was reported that it cannot be used in QSAR if the number of descriptors is extremely larger than the number of data set [29].…”
Section: Introductionmentioning
confidence: 99%